2013
DOI: 10.1111/jmwh.12038
|View full text |Cite
|
Sign up to set email alerts
|

In‐Home HIV Testing and Nevirapine Dosing by Traditional Birth Attendants in Rural Zambia: A Feasibility Study

Abstract: With the substantial shortage of human resources in public health care throughout sub-Saharan Africa, it is extremely valuable to utilize lay health care workers to help extended services beyond the level of the facility. Given the high uptake of PMTCT services we believe that TBAs with proper training and support can successfully provide country-approved PMTCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 24 publications
1
24
1
Order By: Relevance
“…Our estimate was also lower compared to what has been previously reported in other sSA settings[21,23]. The Western Kenya studies were carried out between 2008 and 2011, and before the implementation of free maternity services in 2013[35], which may explain the high estimates in home delivery from Western Kenya.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Our estimate was also lower compared to what has been previously reported in other sSA settings[21,23]. The Western Kenya studies were carried out between 2008 and 2011, and before the implementation of free maternity services in 2013[35], which may explain the high estimates in home delivery from Western Kenya.…”
Section: Discussioncontrasting
confidence: 74%
“…Previous studies across the sSA region report variable prevalence of home deliveries ranging from 9% to 94% amongst women in the general population[8–20], and10% to 53% amongst HIV-infected women[2126]. …”
Section: Introductionmentioning
confidence: 99%
“…TBAs can be an important resource to address the high number of children infected with HIV in Nigeria as well as other Global Plan priority countries (Brennan et al, 2014; Hamela et al, 2014). Researchers have found that after PMTCT training, TBAs were able to test and identify HIV positive pregnant women in rural Zambia and Malawi (Brennan et al, 2014; Hamela et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have found that after PMTCT training, TBAs were able to test and identify HIV positive pregnant women in rural Zambia and Malawi (Brennan et al, 2014; Hamela et al, 2014). Based on these findings, it was concluded that TBAs can play an important role in PMTCT by conducting initial HCT, especially in rural environments.…”
Section: Discussionmentioning
confidence: 99%
“…39 Studies have found that with training, traditional birth attendants are able to administer ART peripartum, enhancing PMTCT. 40 Few intervention studies have targeted critical steps for PMTCT further down the continuum of care, and IS research is needed to improve EID uptake, ARV prophylaxis for exposed newborns, and linkage to care for HIV-infected infants. 41 …”
Section: Discussionmentioning
confidence: 99%